Gonadotropin inhibitory-hormone modulates neurosteroids-synthesizing enzymes expression and aggressive behavior in male sea bass, Dicentrarchus labrax - Paullada-Salmerón, José Antonio; Loentgen, Guillaume Henri; Fuentès, Michaël; Besseau, Laurence; Ubuka, Takayoshi; Mañanos, Evaristo Luis; Muñoz-Cueto, José Antonio (Frontiers in Marine Science, 2023)
Neurosteroids are involved in the regulation of multiple behavioral and physiological processes and metabolic activities in the vertebrate brain. However, central mechanisms of how neurosteroid synthesis is regulated is far to be understood. Gonadotropin-inhibitory hormone (GNIH) is a hypothalamic neuropeptide that negatively regulates gonadotropin secretion but also inhibits sexual and aggressive behaviors in birds and mammals by modulating aromatase enzyme and neuroestrogen synthesis. In a previous study performed in male sea bass, we reported that Gnih inhibited the reproductive axis by acting at the three levels of the brain-pituitary-gonad axis. Moreover, the presence of Gnih cells and fibers in the telencephalon, mesencephalon and rhombencephalon suggests a role of Gnih in regulating other important brain functions in sea bass, including behavior. In this study, we have analyzed the effects of the intracerebroventricular (icv) injection of sbGnih-2 on the brain and pituitary expression of the main neurosteroids-synthesizing enzymes (stAR, cyp17, 3β-hsd, 17β-hsd, cyp19b, cyp7b), as well as on estrogen and androgen receptors (erα, erβ1, erβ2, ar). A combination of immunohistochemistry and in situ hybridization was also used to identify putative interaction of Gnih- and aromatase-positive cells. We also performed a mirror test study as a proxy to measure aggression levels and agonistic behavior after icv injection of sbGnih-2. Central administration of sbGnih-2 at different doses reduced the transcript levels of 3β-hsd and 17β-hsd, and increased the expression of cyp19b (brain aromatase) in the sea bass brain. Neuroanatomical results suggest that paracrine and neuroendocrine actions could mediate Gnih effects on aromatase expression. Central administration of sbGnih-2 also decreased the pituitary expression of 17β-hsd and estrogen receptors (erβ2). The mirror test analysis showed that sbGnih-2 affected the agonistic/aggressive behavior of sea bass as revealed by the decreased interaction with the mirror, lower time spent in the mirror zone, increased latency to establish contact with the mirror and higher mean distance to the mirror zone. In contrast, locomotor activity parameters measured were not affected by sbGnih-2 injection. Taken together, our results showed for the first time in fish that Gnih inhibits social-aggressive behavior and affects the gene expression of neurosteroid-synthesizing enzymes giving rise to neuroandrogens and neuroestrogens in the sea bass brain.